Studies on Antimicrobial and Immunomodulatory Effects of Hot Aqueous Extract of Acacia nilotica L. Leaves against Common Veterinary Pathogens. (7th April 2014) - Sharma, Arvind Kumar; Kumar, Amit; Yadav, Sharad Kumar; Rahal, Anu
Abstract : Acacia nilotica is a plant species that is almost ubiquitously found in different parts of the world. Various preparations of it have been advocated in folk medicine for the treatment of tuberculosis, leprosy, smallpox, dysentery, cough, ophthalmia, toothache, skin cancer as astringent, antispasmodic, and aphrodisiac since immemorial times. The present study investigates the antibacterial, antifungal, antiviral, and immunomodulatory potential of hot aqueous extract (HAE) of Acacia nilotica leaves. On dry matter basis, the filtered HAE had a good extraction ratio (33.46%) and was found to have carbohydrates, glycosides, phytosterols, phenolic compounds, saponins, and flavonoids as major constituents. HAE produced dose dependent zone of inhibition against Klebsiella pneumoniae, Pseudomonas aeruginosa, E. coli, Bacillus cereus, Staphylococcus aureus, and Streptococcus uberis and fungal pathogens Aspergillus niger and Aspergillus fumigates ; however, no antiviral activity was recorded against IBR virus. HAE of A. nilotica revealed both proliferative and inhibitory effects on the rat splenocytes and IL-10 release depending on the dose. Detailed studies involving wide spectrum of bacterial, fungal, and viral species are required to prove or know the exact status of each constituents of the plant extract.